Training and Mentoring Interior Production Based on CNC Router at Miftahul Huda Al-Burhani Islamic Boarding School Plered Purwakartad on CNC Router At Miftahul Huda Al-Burhani Islamic Boarding School Plered Purwakarta Regency - Roni Wibowo, Nanang; Nulhakim, Lukman; Kurnia , Deni (Society : Jurnal Pengabdian Masyarakat, 2026)
Miftahul Huda Al-Burhani Islamic Boarding School is one of the Islamic boarding schools that teaches religious knowledge, especially yellow books, also teaches agricultural, livestock, and fisheries knowledge as well as specialization/skill education in the form of interior skills. The interior business unit under the head of the Islamic boarding school business management has produced interior products made of multiplex and HPL which are produced and marketed conventionally. Through community service activities (PKM) it seeks to help improve the production sector in terms of product diversity and the marketing sector in terms of the ability to design marketing strategies. The method used in solving partner problems in the production sector is providing appropriate CNC Router technology in the production process and training in design applications using Vetric Aspire and implementation using CNC Router. The completion of the marketing sector is carried out training in creating marketing tools using Canva and creating online marketing media such as on YouTube, TikTok, and creating online stores on Tokopedia, Shopee so that market reach becomes wider. The targeted output of this activity is product diversity and increased ability to design marketing strategies. The results obtained are the ability to innovate in making carved products, calligraphy, and others using CNC Router machines and the ability to create product catalogs using Canva.